2006
DOI: 10.1007/s11010-005-9113-3
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Proliferation and Differentiation of Neural Progenitor Cells Isolated from Postnatal and Adult Mice Brain by Wnt-3a and Wnt-5a

Abstract: Wnt signaling is implicated in the control of cell growth and differentiation during CNS development. These findings are based on studies of mouse and chick models. However, the action of Wnt signaling, at the cellular level, is poorly understood. In this study, we investigated the roles of Wnt-3a and Wnt-5a on differentiation and proliferation of postnatal neural progenitor cells (NPCs) in mice.NPCs were isolated from the subventricular zone (SVZ) of PN-1 and adult ICR mice. Plasmids containing active Wnt-3a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 38 publications
3
70
0
1
Order By: Relevance
“…Wnt1, Wnt3, Wnt3a, Wnt4, Wnt5a), we sought to identify the Wnt ligand(s) responsible for this effect by employing a series of Wnt treatment experiments. Wnt3a is known to promote neuronal differentiation of NPCs of the forebrain and spinal cord (Kalani et al, 2008;Lie et al, 2005;Muroyama et al, 2002;Yu et al, 2006). Our in vitro study showed that Wnt3a promotes GABAergic neuron differentiation and that Ryk receptor is required for this effect.…”
Section: Activity Of Ryk-mediated Wnt Signaling In the Ventral Telencmentioning
confidence: 53%
See 1 more Smart Citation
“…Wnt1, Wnt3, Wnt3a, Wnt4, Wnt5a), we sought to identify the Wnt ligand(s) responsible for this effect by employing a series of Wnt treatment experiments. Wnt3a is known to promote neuronal differentiation of NPCs of the forebrain and spinal cord (Kalani et al, 2008;Lie et al, 2005;Muroyama et al, 2002;Yu et al, 2006). Our in vitro study showed that Wnt3a promotes GABAergic neuron differentiation and that Ryk receptor is required for this effect.…”
Section: Activity Of Ryk-mediated Wnt Signaling In the Ventral Telencmentioning
confidence: 53%
“…Wnt3a has been shown to bind to Ryk receptor to promote neurite outgrowth (Lu et al, 2004), and Wnt3a can induce neuronal differentiation of NPCs in both the forebrain and spinal cord (Kalani et al, 2008;Lie et al, 2005;Muroyama et al, 2002;Yu et al, 2006). Wnt3a has recently been shown to upregulate gene expression of the oligodendrocyte inhibitors Id2 and Id4, and to downregulate expression of myelin genes such as MBP in hippocampus-derived adult neural progenitor cells and oligodendroglial cell cultures (Ye et al, 2009).…”
Section: The Ryk Receptor Is Required For Wnt3a-induced Gabaergic Neumentioning
confidence: 99%
“…In vitro studies have shown that WNT3A and WNT5A promote proliferation and neuronal differentiation of SVZ-derived NSC cultures (Yu et al 2006), and transcripts for these factors have been identified in the V-SVZ and adult OB (Shimogori et al 2004;Lim et al 2006;Ramos et al 2013). The canonical Wnt signaling pathway involves the binding of WNT to Frizzled (Fz) receptors, which leads to stabilization of b-catenin protein, its nuclear translocation, and function as a transcriptional coactivator.…”
Section: Wnt Signaling In the V-svzmentioning
confidence: 99%
“…Wnt3 and Wnt7a specif-ically favor neuronal differentiation of late, but not of early, cortical NPCs (Hirabayashi et al, 2004;Hirabayashi and Gotoh, 2005;Yu et al, 2006), and Wnt5a stimulates the differentiation of dopaminergic neurons (Castelo-Branco and Arenas, 2006;Andersson et al, 2008). As Wnt ligands elicit such a variety of responses, their functions need to be determined in a cell type-and context-dependent manner.…”
Section: Introductionmentioning
confidence: 99%